Relevance of physicochemical characterization in nanotoxicology studies - Louro, Henriqueta (2016)
Nanomaterials (NMs) with the same chemistry can greatly differ by size, surface area, shape, stability, rigidness, coating or electrical charge and these characteristics affect nano-bio interactions, leading to different toxic potential. In this communication is shown that closely related NMs can have different genotoxic effects, evidencing the importance of investigating the toxic potential of each NM individually, instead of assuming a common mechanism and equal genotoxic effects for a set of similar NMs. The importance of considering complexity of in vivo systems in nanotoxicology, such as the use of tridimensional cellular models, air-liquid interface exposure or in vivo models that mimic human routes of exposure, is underlined.